2022
DOI: 10.3390/life12111773
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × Environment Interaction and Stability Analysis of Commercial Hybrid Grain Corn Genotypes in Different Environments

Abstract: The introduction of superior grain corn genotypes with high and stable yield (YLD) in most environments is important to increase local production and reduce dependency on imported grain corn. In this study, days to tasseling (DT), plant height, and YLD of 11 grain corn genotypes were observed in 10 environments to evaluate the effects of genotype (G), environment (E), and genotype by environment interactions (GEI) using GGE analysis and the stability of genotypes using stability parameters. In each location, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
2
4
0
2
Order By: Relevance
“…This pattern aligns with findings from Adham et al. ( 2022 ), Bilate Daemo et al. ( 2023 ), Esan et al.…”
Section: Discussionsupporting
confidence: 92%
“…This pattern aligns with findings from Adham et al. ( 2022 ), Bilate Daemo et al. ( 2023 ), Esan et al.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the effects of environment, genotype, and GEIs on maize yield were significant (p < 0.01), and the environmental factor contributed more variation (49.96%) than genotypes and GEIs, reflecting that there was a greater variability in the environment (Table 3). Similar results were found in Adham et al, Alizadeh et al, and Ansarifard et al that the environment accounted for most of the variance [16,35,36]. Additionally, the GEI effect is largely a response to environmental factors, not genotypic factors [37]; thus, the significant GEI factors demonstrated that the use of AMMI and the GGE biplot was appropriate in yield evaluation [38].…”
Section: Yield Performance Evaluationsupporting
confidence: 85%
“…Se realizó un gráfico Biplot (Figura 1) con las puntuaciones de los 2 ejes principales correspondientes a los PCA del análisis Biplot GGE-SReg, el cual, permitió visualizar explícitamente el desempeño de los genotipos evaluados dentro del entorno (cuál-ganó-dónde). De acuerdo con este análisis se formaron 3 grupos ambientales potenciales, resultados similares obtuvieron otros autores en tomate (Djidonou et al 2020) y otros cultivos (Adham et al 2022, Lima et al 2023. El primero fue el ambiente de Villa Lourdes en el cual el genotipo más sobresaliente fue el G14 (T7.RA-15-EN9-7); el segundo estuvo conformado por las localidades de Albina Grande, Tres Quebradas y El Ejido en el cual el cultivar con mejor comportamiento fue el G3 (ICLN-1) y el tercer grupo ambiental y menos productivo debido a la gran cantidad de patógenos de suelo, se identificó para La Villa en el cual el genotipo 9 (DINA.RB-17-EN21-2) presentó un mejor desempeño.…”
Section: Análisis Del Desempeño De Los Genotipos En Los Diferentes Am...unclassified
“…Si un entorno tiene una alta capacidad de discriminación y representatividad genotípica, entonces es un entorno ideal (Adham et al 2022). Con base en el Biplot de capacidad de discriminación y representatividad, ningún ambiente del estudio ocupa la primera posición en ambos análisis.…”
Section: Comportamiento De Los Ambientesunclassified